Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Anonymous
Anonymous asked in Science & MathematicsMathematics · 10 years ago

How to differentiate this function f(x)=(x + 1)^3 (x − 3)^3?

Please show me the steps to differentiate this polynomial function!

8 Answers

Relevance
  • Anonymous
    10 years ago
    Favorite Answer

    f(x) = (x^2 - 2x - 3)^3 ---> f '(x) = 3(2x-2)(x^2-2x-3)^2

  • 10 years ago

    d [f(x)] = 3(x+1)^2 x 3(x-3)^2 (differentiation final answer)

  • Anonymous
    10 years ago

    1)y =(x+1)^3 into (x-^3

    2) u =( x + 1 )^3

    3) v =(x-3)^3 4)dy/dx =(v)du/dx+(u)dv/dx . 5)you have to treat x+1 as x and differentiate u ., then differentiate x+1 and multiply with t . Wait i'l show you how .if you differentiate x^3 you wil get 3x^2 , put x+1 instead of x in t . du/dx =3 (x+1)^2 .

    6)similarly if u diff. V you 'll get

    dv/dx =3(x-3)^2 .

    7)now substitute du/dx and dv/dx in the formula .

    8)dy/dx=[ (x-3)^3 (3)(x+1)^2 ] + [ ( x+1)^3 (3)(x-3)^2 ]

    9)dy/dx=[ 3x^5 -21x^4+30x^3+216x^2+243x+81 ] + [3x^5-9x^4-12x^3 +36x^2 +72x+27]

    10)dy/dx=(6x^5)-(30x^4)+(18x^3)+(252x^2)+(315x)+108 . Pshew . . . Its done . 27]

    10)dy/dx=(6x^5)-(30x^4)+(18x^3)+(252x^2)+(315x)+108 . Pshew . . . Its done .

  • 10 years ago

    LET y= (x+1)^3 (x- 3)^3

    dy/dx = (x--3)^3 d/dx(x+1)^3 + (x+1)^3 d/dx( x-3)^3

    = (x-3)^3 3( x+1)^2 *d/dx(x+1)+ ( x+1)^3 3(x-3)^2 *d/dx(x-3)

    = 3(x-3)^3(x+1)^2*1 + 3(x+1)^3 (x-3)^2 *1

    = 3(x-3)^2 (x+1)^2 [ x-3 +x+1 ]

    =3 (x-3)^2 (x+1)^2 [2x-2 ]

    = 6 (x-3)^2(x+1)^2 (x-1) ans

  • How do you think about the answers? You can sign in to vote the answer.
  • Anonymous
    10 years ago

    Apply product rule first

    ans=(x+1)^3 . d((x-3)^3)+ d((x+1)^3) . (x-3)^3 = (x+1)^3 .3(x-3)^2 . 1 + 3. (x+1)^2 . (x-3)^3

    now expand and find out last result...

  • 10 years ago

    after differeniating the above eq the answer is

    6(x^2-1)^5*2x

  • Anonymous
    5 years ago

    Take the derivative, set it equal to zero, and solve for x. Then take the second derivative, and plug in all solutions for x. Wherever f'' is less than zero, this is a local max. Wherever f'' is greater than zero, this is a local min. Wherever f'' is zero, this is a saddle point.

  • 10 years ago

    y = [(x + 1)^3] [(x − 3)^3]

    Diff. w. r. t. x, we get,

    d/dx(y) = d/dx { [(x + 1)^3] [(x − 3)^3] }

    Therefore, dy/dx = { [(x + 1)^3] d/dx [(x − 3)^3] } + { [(x − 3)^3] d/dx [(x + 1)^3] }

    dy/dx = { [(x + 1)^3](3)[(x − 3)^2](1) } + { [(x − 3)^3] 3 [(x + 1)^2] (1) }

    dy/dx = (3) [(x+1)^2] [(x-3)^2] [ (x + 1) + (x - 3) ]

    dy/dx = (3) [(x+1)^2] [(x-3)^2] [ (x - 2) ]

    Final Answer :

    dy/dx = (3) [(x+1)^2] [(x-3)^2] [ (x - 2) ]

    Happy to help. :)

Still have questions? Get your answers by asking now.